Development and initial validation of a clinical measure to assess symptoms of post-stroke depression in stroke patients at the rehabilitation stage - Chen, Junya; Liu, Jing; Zeng, Yawei; Li, Ruonan; Wang, Yucui; Ding, Weiwei; Guo, Junyi; Lin, Haiyun; Li, Jufang (Frontiers in Psychology, 2022)
Abstract Background: The high incidence of post-stroke depression (PSD) at the rehabilitation exerts a negative effect on the treatment and functional recovery of stroke patients and increases the risk of mortality. It is necessary to screen PSD in the rehabilitation stage and thus provide effective intervention strategies. However, existing measurements used to assess PSD in the rehabilitation stage stroke patients are in lack of specificity. This study aimed to develop a clinical measure to assess symptoms of PSD in the rehabilitation stage. Methods: The research team created the initial items by a literature review and semi-structured interview of the stroke patients. Then the symptom-related items were estimated by three panels: healthcare professionals (N = 41), Delphi experts (N=15), and stroke patients in the rehabilitation stage (N = 30). Results: The literature review and semi-structured interview produced 51 symptom-related items including six domains and the items were reduced to 47 by the healthcare professionals. The symptom-related items were further reduced to 33 items by a two-round Delphi consultation. The initiative coefficients of the two Delphi rounds were 71.4% and 100%, the expert authority coefficients were both 0.85, the Kendall’s W were 0.152 and 0.408 (p < 0.01), and the coefficient of variation (CV) were 0.05-0.32 and 0.00-0.18, respectively. The item-level content validity index (I-CVI) were 0.53-1.00, the scale-level CVI/universal agreement (S-CVI/UA) was 0.26, and the S-CVI/average (S -CVI/Ave) was 0.85 for the first found Delphi consultation; the I-CVI were 0.67-1.00, the S-CVI/AU was 0.61, and the S-CVI/Ave was 0.97 for the second round Delphi consultation. All content validity indicators have been significantly improved compared with the first round. Using mean ≥ 4 and full score ≥ 0.5, combined with CV ≤ 0.16 as the item criteria, a clinical measure of PSD with 33 items and 6 dimensions (cognition, sleep, behavior, emotion, body, and guilt) was finally formed after two rounds. And the stroke patients made no further revisions after evaluation. Conclusions: The research team developed a specific tool with good content validity to assess the symptoms of PSD in the rehabilitation stage.